DIDACTIC CONDITIONS OF FORMATION IN JUNIORS SCHOOLCHILDREN’S ABILITY TO WORK WITH A TEXTBOOK - Bilokonna, N.I. (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the problem of forming some skills in using textbook by junior schoolchildren. Some didactic conditions which favour the increase in efficiency of using textbook by junior schoolchildren are determined here.